Strategi Pengembangan Pariwisata Malino Di Kabupaten Gowa - Muhammad, Adam; Hakim, Lukman; Fatmawati, Fatmawati (Universitas Muhammadiyah Makassar, 2021)
This study purposedto identify the strategy for developing and implementing the strategy carried out by the Department of Tourism and Culture of Gowa Regency in the development of tourism objects in the Malino. This study used descriptive qualitative method. The number of informants in this study were 5 people. The type of data consisted of primary data obtained through interviews and observations, while secondary data were obtained from report documents and regulations. The results of this study showed that the development strategy undertaken by the Department of Tourism and Culture of Gowa Regency was a strategy as a plan for the implementation of the identified development strategies such as the aspects of attraction, aspects of accessibility, access to amenities, and aspects of additional services must continue to develop the availability of aspects Accessibility, amenities and Anciliary Service were sufficiently supportive but still needed to be developed in terms of special transportation that connected tourism objects, tourism information centers, money chergers, theater buildings, and several roads that still needed to be improved so that tourists who were visiting Malino felt comfortable. Keywords: Strategy, Tourism Development